Mempertanyakan Materi Muatan Peraturan Daerah Nomor 3 Tahun 2004 Tentang Larangan Pelacuran dan Pornografi di Kabupaten Sambas - Tamrin Muchsin; Sri sudono Saliro (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
The regional government in the framework of implementing regional autonomy has the authority and independence in regulating regional government affairs. The authority of regional governments to regulate self-government affairs as stipulated in Law Number 23 Year 2014, hierarchically is a juridical implementation of Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia after the second amendment, which reads: “Government provinces, regencies and cities regulate and manage government affairs by themselves according to the principles of autonomy and assistance tasks ”. The local government of Sambas Regency in carrying out government affairs under its authority has the right to make policies both in the context of improving services, in order to increase community participation in regional development and in order to maintain moral values in people's lives. One of the important elements in implementing this process is through the formation of local regulations. A dynamic that can occur with regard to the making of regional regulations is the linkage between local political interactions and the technicality of making laws and regulations, the boundaries of which must not conflict with the 1945 Constitution, as well as the laws and regulations above. The presence of Sambas Regency Regional Regulation Number 3 of 2004 concerning the prohibition of prostitution and pornography is contrary to higher-level laws and regulations so that this regional regulation must be repealed.